2023
DOI: 10.1101/2023.01.18.524407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High-throughput sequencing of macaque basolateral amygdala projections reveals dissociable connectional motifs with frontal cortex

Abstract: The basolateral amygdala (BLA) projects widely across the macaque frontal cortex, and amygdalo-frontal projections are critical for optimal emotional responding and decision-making. Yet, little is known about the single-neuron architecture of these projections: namely, whether single BLA neurons project to multiple parts of the frontal cortex. Here, we use MAPseq to determine the projection patterns of over 3000 macaque BLA neurons. We found that one-third of BLA neurons have two or more distinct targets in pa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…That is, within each node are related neurons which share common targets. For example, viral barcode analysis of amygdala-prefrontal connectivity has shown that single amygdala BLA neurons can connect with one to several neurons in different parts of prefrontal cortex (Zeisler et al, 2023). This raises a potential scenario in which dynamics of mesoscale nodal selection is further coupled with intra-node single neuron selection to achieve a broad range of distinct and specific functional circuits.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, within each node are related neurons which share common targets. For example, viral barcode analysis of amygdala-prefrontal connectivity has shown that single amygdala BLA neurons can connect with one to several neurons in different parts of prefrontal cortex (Zeisler et al, 2023). This raises a potential scenario in which dynamics of mesoscale nodal selection is further coupled with intra-node single neuron selection to achieve a broad range of distinct and specific functional circuits.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the connectivity of these nuclei is quite heterogeneous, appropriate for supporting a broad spectrum of behavioral axes (Klein-Flügge et al, 2022; Scangos et al, 2021). Not only does each nucleus have distinctive cell types and cell densities (Yu et al, 2023), even single neurons within a subdivision of the amygdala exhibit distinct targeting patterns, projecting to either 1, 2, 3, or 4 cortical sites (Zeisler et al, 2023). Electrical stimulation of nuclear-specific targets in the human amygdala combined with neuroimaging revealed the existence of multiple distinct networks and a reproducible temporal pattern of activation (Sawada et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…However, in previous work (Huang et al, 2020) we have barcoded more than 100,000 neurons in a single brain, and there is no technical barrier to labeling comparable numbers of neurons for axonal BARseq in future studies. Furthermore, Sindbis virus can infect diverse species including primates (Zeisler et al, 2023), so axonal BARseq could potentially be modified to map projections in many model systems, especially those in which conventional tracing-based approaches are impractical. Axonal BARseq thus has the potential to emerge as a powerful tool for massively multiplexed mapping of single neuron projections in diverse model systems.…”
Section: Limitations and Future Developmentsmentioning
confidence: 99%
“…However, because spatial resolution in MAPseq is limited by the dissection of brain areas prior to bulk sequencing, axonal projection patterns in this MAPseq/BARseq combined approach can only be crudely resolved. MAPseq and BARseq have been repeatedly validated using multiple methods in a wide range of brain areas (Zeisler et al 2023; Y. Chen et al 2022; Hausmann et al 2022; Tsoi et al 2022; Webb et al 2022; Klingler et al 2021; Mathis et al 2021; Muñoz-Castañeda et al 2021; Sun et al 2021; Gergues et al 2020; Huang et al 2020; X.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation